Methods For Enhancing The Lexical Competence Of Future English Teachers:A Pedagogical Challenge (Journal of Pedagogical Inventions and Practices, 2024)
Developing the lexical competence of future English teachers is a critical pedagogical challenge, particularly in non-native English-speaking contexts. Lexical competence, defined as the ability to understand, produce, and use vocabulary effectively, is central to language teaching and learning. However, many teacher training programs fail to address this component comprehensively, often focusing on general language proficiency rather than specialized vocabulary teaching strategies. This study explores innovative methods for enhancing lexical competence among pre-service English teachers, using a mixed-methods research approach. The research involved 60 participants from teacher training institutions in Uzbekistan, who underwent a 12-week training program that integrated digital tools, collaborative learning strategies, and culturally relevant materials. Quantitative data from pre- and post-intervention assessments showed significant improvement in participants’ vocabulary size and teaching confidence. Qualitative insights from interviews highlighted the effectiveness of gamified tools and peer activities in motivating learners and promoting vocabulary retention. The study emphasizes the importance of integrating technology, fostering collaboration, and incorporating cross-cultural dimensions into teacher education programs. It also addresses the challenges, such as limited access to authentic materials and language anxiety, that hinder the development of lexical competence. These findings provide a framework for enhancing the quality of English teacher training, with implications for improving both language proficiency and pedagogical effectiveness in diverse educational contexts.